Refugiados no contexto das mudanças ambientais - Costa, Claudia Silvana da (2016)
This thesis aims to focus on the construction of a subject called environmental refugee, new social group s formation that came from an adverse context, caused by the damaging effects of climate changes at its land which became inhabitable and inhospitable. Like that, unlike other refugees who leaved their countries for political, ethnic-religious, economical or social reasons, environmental refugees unwittingly has to leave their countries once in their lands has no way of survival because of the deleterious effects caused by climate change that are in the process, making certain territorial bases in social production and identity of peoples. Accordingly to the United Nations (UN) data, the number of environmental refugees on the planet will increase significantly over the next few years, mostly will come from Africa and from its other small Islands, which are those with greater vulnerability to the impacts of climate changes because of their geographical location, becoming like that, the potential environmental refugees. This way, trying to contribute to build a larger problematic for this matter inside a context that shows how necessary is to designate a definition that fits ruight this kind of refugees and to build a new legal framework guaranteeing to this group human being conditions, taking by example the case of São Tomé e Príncipe, small African s Island considered as States, with the clipping sample of Ilha de São Tomé, which is already under the risks of climate effects on its territory and with potential environmental refugees, providing like that, a reflection about the challenges of the environmental refugees, placing them on the spot of the legal Constitution.